2010
DOI: 10.1002/hipo.20863
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala gene expression of NMDA and GABAA receptors in patients with mesial temporal lobe epilepsy

Abstract: ABSTRACT:Temporal lobe epilepsy (TLE) is the most common form of partial epilepsy and affects 40% of the patients. Seizures arising from the mesial temporal lobe structures (i.e., amygdala and hippocampus) are common, whereas neocortical seizures are rare. In recent years, many studies aimed to identify the pattern of gene expression of neurotransmitters involved in molecular mechanisms of epilepsy. We used real-time PCR to quantify the expression of GABA A (subunits a1, b1, b2) and NMDA (subunits NR1, NR2A, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
12
0
4
Order By: Relevance
“…One noteworthy exclusion criterion for our tissue was seizure as the primary cause of death. Seizures are a co‐morbid feature of ASD (Keller, Basta, Salerno, & Elia, ), often originating in the temporal lobe (de Moura et al, ) and have been shown to impact dendritic morphology and spine density (Yilmazer‐Hanke et al, ; Aliashkevich et al, ). In the present study, we received tissue from multiple brain banks and only had clinical records for a handful of ASD cases (3 of 16), therefore not enough to analyze our findings in terms of correlating spine density with symptom severity, although we hope to include this in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One noteworthy exclusion criterion for our tissue was seizure as the primary cause of death. Seizures are a co‐morbid feature of ASD (Keller, Basta, Salerno, & Elia, ), often originating in the temporal lobe (de Moura et al, ) and have been shown to impact dendritic morphology and spine density (Yilmazer‐Hanke et al, ; Aliashkevich et al, ). In the present study, we received tissue from multiple brain banks and only had clinical records for a handful of ASD cases (3 of 16), therefore not enough to analyze our findings in terms of correlating spine density with symptom severity, although we hope to include this in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In pilocarpine rat model of epilepsy, which closely resembles MTLE in humans, it has been shown that there is time-dependent increase in the protein levels of NR1 subunit of NMDA receptor (Lopes et al, 2013). It has also been reported that in brain tissues obtained from patients with MTLE there is up regulation of NR1 subunit, which contributes to the hyperexcitable neuronal network (de Moura et al, 2012). A study involving tissue specimens obtained from patients with glioma displaying tumour-associated seizures suggests higher glutamate concentration and increased expression of glutamate transporters (Yuen et al, 2012) further supporting the role of enhanced endogenous glutamate receptor activity in seizure generation.…”
Section: Resultsmentioning
confidence: 99%
“…☉ indicates P<0.05, ★ indicates P<0.01). Research Guofeng Wu [37]. Although traditional surgery by selectively ablating the anterior lobe or the amygdalahippocampus could achieve favourable results, up to 30% of TLE cases are unsuitable for resective neurosurgery [3].…”
Section: Discussionmentioning
confidence: 99%